The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/ar2661
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans induces cyclo-oxygenase 2 expression and prostaglandin E2 production in synovial fibroblasts through an extracellular-regulated kinase 1/2 dependent pathway

Abstract: Introduction Synovial cells are potential sources of inflammatory mediators in bacterial-induced arthritis but their involvement in the inflammatory response to Candida albicansinduced septic arthritis is largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Second, we found upregulated PGE 2 in Mc‐infected cells, which was inhibited by pre‐exposure to WCS. Our finding of increased PGE 2 production following an infection is in line with previous work 24,25 . However, reduction of PGE 2 in both WCS‐ and Mc‐treated cells does not appear to support the clinical observation of increased PGE 2 levels in COPD patients.…”
Section: Discussionsupporting
confidence: 82%
“…Second, we found upregulated PGE 2 in Mc‐infected cells, which was inhibited by pre‐exposure to WCS. Our finding of increased PGE 2 production following an infection is in line with previous work 24,25 . However, reduction of PGE 2 in both WCS‐ and Mc‐treated cells does not appear to support the clinical observation of increased PGE 2 levels in COPD patients.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, Candida can activate host cells to produce prostaglandins (Gagliardi et al, 2010; Lee et al, 2009). Prostaglandins such as prostaglandin E 2 (PGE 2 ) enhance allergic inflammation (Church et al, 2012), suggesting a possibility that overgrowth of gut fungal microbiota may alter immune responses via PGE 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We provided the evidences that the elevated PGE 2 level induced by gut fungal overgrowth is involved in airway inflammation via macrophage polarization into alternative M2 type. In vitro studies suggested that Candida not only produce PGE 2 in itself (Noverr et al, 2001; Noverr et al, 2002) but also induce PGE 2 production from host cells (Gagliardi et al, 2010; Lee et al, 2009). We showed that Abx-treatment significantly increased the PGEM levels in Ptges -/- mice (Figure 4E), suggesting that the increased PGE 2 might not be derived from host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, enhanced PGE2 levels after prolonged Abx treatment was accompanied by overgrowth of a colonized fungal Candida species in the gut (without causing systemic candidemia). However, adjunctive antifungal agent administration to Abx-treated mice diminished serum PGE2 levels (35), whereas Candida not only produced PGE2 but also promoted PGE2 production from host cells (64,65). Given that Candida infections are not uncommon in OLT (66) and that the role of colonized gastrointestinal fungi in transplantation remains poorly Although EP4 antagonism diminished cytoprotective features (inhibition of ER stress, enhancement of autophagy) in our in vitro (hepatocyte cultures) and in vivo (IR-stressed OLT) studies, we acknowledge that the recipient Abx regimen might indirectly protect hepatocytes by inhibiting proinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%